Recent Developments in the Study of Plant Microbiomes - Glick, Bernard R.; Gamalero, Elisa (Microorganisms (Basel), 2021)
To date, an understanding of how plant growth-promoting bacteria facilitate plant growth has been primarily based on studies of individual bacteria interacting with plants under different conditions. More recently, it has become clear that specific soil microorganisms interact with one another in consortia with the collective being responsible for the positive effects on plant growth. Different plants attract different cross-sections of the bacteria and fungi in the soil, initially based on the composition of the unique root exudates from each plant. Thus, plants mostly attract those microorganisms that are beneficial to plants and exclude those that are potentially pathogenic. Beneficial bacterial consortia not only help to promote plant growth, these consortia also protect plants from a wide range of direct and indirect environmental stresses. Moreover, it is currently possible to engineer plant seeds to contain desired bacterial strains and thereby benefit the next generation of plants. In this way, it may no longer be necessary to deliver beneficial microbiota to each individual growing plant. As we develop a better understanding of beneficial bacterial microbiomes, it may become possible to develop synthetic microbiomes where compatible bacteria work together to facilitate plant growth under a wide range of natural conditions.